Aluminum-based silicon carbide composite plate strip
By adopting multi-layer structural design and composite reinforcement materials in aluminum-based composite sheets, the problem of limited performance improvement of traditional aluminum-based composite sheets is solved, and significant mechanical properties and thermal stability are achieved, which are suitable for multiple high-performance areas.
Patent Information
- Application Number
- CN202411712616.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional aluminum-based composite panels adopt simple laminated structures and a single type of reinforcement material, resulting in limited improvement in the overall performance of the material, limiting its wide application.
The structural design of aluminum-based silicon carbide composite plate strip is adopted, including a base layer, a porous structural layer, a reinforcement layer and a protective coating. Each layer is composed of an aluminum matrix and a composite reinforcement material. The high-quality preparation of the material is ensured through thermal isostatic sintering, powder metallurgy and 3D printing.
It significantly improves the mechanical properties and thermal stability of the materials, enhances the overall mechanical properties, has significant technical advantages and application value, and is suitable for aerospace, automobile manufacturing, rail transit and other fields.
Smart Images

Figure CN119502478A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal material preparation, and more specifically to an aluminum-based silicon carbide composite plate strip. Background Art
[0002] With the rapid development of modern industrial technology, the demand for high-performance and lightweight materials is growing. Aluminum-based composite plates, as an advanced composite material that combines the light weight and high toughness of aluminum alloys with the high strength and high stiffness of reinforced materials, are widely used in aerospace, automobile manufacturing, rail transportation, electronic communications and other fields. However, traditional aluminum-based composite plates still have shortcomings in mechanical properties, thermal stability and corrosion resistance, and it is difficult to meet the increasingly high performance requirements.
[0003] Traditional aluminum-based composite plates usually adopt a simple stacking structure, and the reinforcement material is often limited to a single particle or fiber type, resulting in limited improvement in the comprehensive performance of the material, which limits the wide application of aluminum-based composite plates. In view of this, we propose an aluminum-based silicon carbide composite plate strip. Summary of the invention
[0004] The purpose of the present invention is to provide an aluminum-based silicon carbide composite plate strip, aiming to solve the problem that traditional aluminum-based composite plates usually adopt a simple stacking structure, and the reinforcing materials are often limited to a single particle or fiber type, resulting in limited improvement in the comprehensive performance of the material, which limits the wide application of aluminum-based composite plates.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: an aluminum-based silicon carbide composite plate strip, which includes, from the inside to the outside, a base layer, a porous structure layer, a strengthening layer and a protective coating:
[0006] The base layer and the strengthening layer are both composed of an aluminum matrix and a composite reinforcement material;
[0007] The aluminum matrix of the base layer is an aluminum-magnesium-silicon alloy, and the addition amount of magnesium is 3-7%, the addition amount of silicon is 7-11%, and the rest is aluminum and unavoidable impurities.
[0008] The composite reinforcement material of the base layer comprises, by volume fraction, 10-20% of SiC particles, 0.3-0.7% of carbon nanofibers, 0.1-0.2% of graphene nanosheets, and 3-5% of alumina short fibers;
[0009] The aluminum matrix of the strengthening layer is an aluminum-zinc-magnesium-copper alloy, and the addition amount of zinc is 8-12%, the addition amount of magnesium is 2-4%, the addition amount of copper is 1-3%, and the rest is aluminum and unavoidable impurities.
[0010] The composite reinforcement material of the strengthening layer comprises, by volume fraction, 25-35% of SiC particles, 5-10% of barium titanate particles, 8-12% of boron nitride fibers, 0.3-0.6% of carbon nanofibers and 0.15-0.25% of graphene nanosheets, and 2-4% of zirconium oxide particles;
[0011] The porous structure layer is composed of a three-dimensional porous skeleton made of 7075 aluminum alloy;
[0012] The aluminum matrix and the composite reinforcement material are bonded by means of a polyimide resin containing 10% of glass fiber.
[0013] Preferably, the polyimide resin containing glass fibers is composed of a polyimide resin matrix, glass fibers and a small amount of curing agent, wherein the content of the glass fibers is 10%, and the amount of curing agent added is determined according to the curing requirements of the resin.
[0014] Preferably, the aluminum matrix raw materials of the base layer and the strengthening layer need to be homogenized before preparation to improve the distribution uniformity of the alloy elements.
[0015] Preferably, the three-dimensional porous skeleton of the porous structure layer is prepared by powder metallurgy or 3D printing technology, and has uniform porosity and good mechanical properties.
[0016] A method for preparing an aluminum-based composite plate according to any one of the above, the method comprising the following steps:
[0017] S1: Raw material preparation and pretreatment: Prepare the raw materials of the base layer, porous structure layer, strengthening layer and protective coating according to the ratio, and clean and pretreat the raw materials;
[0018] S2: Preparation of base and reinforcement layer blanks: The aluminum matrix raw materials of the base and reinforcement layers are uniformly mixed with the corresponding composite reinforcement materials, and are prepared into blanks by hot pressing sintering or powder metallurgy process;
[0019] S3: Preparation of porous structure layer: Prepare a three-dimensional porous skeleton of 7075 aluminum alloy by powder metallurgy or 3D printing technology to form a porous structure layer;
[0020] S4: Lamination and pre-pressing: The base layer, the porous structure layer and the reinforcement layer are stacked in order, and polyimide resin containing glass fiber is evenly applied between the layers as a binder, and then pre-pressing is performed;
[0021] S5: Curing: Curing the pre-pressed sample at an appropriate temperature and pressure to completely cure the polyimide resin containing glass fibers;
[0022] S6: Heat treatment: The cured sample is heat treated to improve its mechanical properties and thermal stability;
[0023] S7: Protective coating treatment: The surface of the aluminum-based composite sheet after heat treatment is treated with aluminum-zinc alloy to improve its corrosion resistance and aesthetics.
[0024] Preferably, in step S2, the base layer and the strengthening layer are prepared by hot isostatic pressing sintering process, and the sintering is carried out at a temperature of 1300-1500° C. and a pressure of 150-250 MPa.
[0025] Preferably, in step S4, the pre-pressing pressure is 20-40 MPa, and the pre-pressing time is 30-60 minutes.
[0026] Preferably, in step S6, the heat treatment includes two steps of solution treatment and aging treatment, the solution treatment temperature is 480-520°C, and the holding time is 24 hours; the aging treatment temperature is 160-200°C, and the holding time is 48 hours.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. The present invention divides the composite plate and strip into a base layer, a porous structure layer, a strengthening layer and a protective coating in sequence. The base layer and the strengthening layer are both composed of an aluminum matrix and a composite reinforcement material, wherein the aluminum matrix is an aluminum-magnesium-silicon alloy and an aluminum-zinc-magnesium-copper alloy, respectively, and the composite reinforcement material comprises a variety of high-performance materials such as SiC particles, carbon nanofibers, and graphene nanosheets. The porous structure layer is composed of a three-dimensional porous skeleton made of 7075 aluminum alloy, which enhances the overall mechanical properties of the material, and significantly improves the mechanical properties and thermal stability of the material by optimizing the material composition and structure, and has significant technical advantages and application value.
[0029] 2. The present invention adopts aluminum alloy as the base material, achieving a lightweight design of the material.
[0030] 3. The present invention adopts advanced technologies such as hot isostatic pressing, powder metallurgy and 3D printing to ensure high-quality preparation of materials.
[0031] 4. The present invention is applicable to a variety of fields such as aerospace, automobile manufacturing, rail transportation, etc., and has broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a flow chart of the method mentioned in Example 1 of the present invention. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0034] The present invention divides the composite plate and strip into a base layer, a porous structure layer, a strengthening layer and a protective coating in sequence. The base layer and the strengthening layer are both composed of an aluminum matrix and a composite reinforcing material, wherein the aluminum matrix is an aluminum-magnesium-silicon alloy and an aluminum-zinc-magnesium-copper alloy, respectively, and the composite reinforcing material comprises a variety of high-performance materials such as SiC particles, carbon nanofibers, and graphene nanosheets. The porous structure layer is composed of a three-dimensional porous skeleton made of 7075 aluminum alloy, which enhances the overall mechanical properties of the material, and significantly improves the mechanical properties and thermal stability of the material by optimizing the material composition and structure, and has significant technical advantages and application value.
[0035] Embodiment 1:
[0036] like Figure 1 As shown, the present invention relates to an aluminum-based silicon carbide composite plate strip, which includes, from the inside to the outside, a base layer, a porous structure layer, a strengthening layer, and a protective coating:
[0037] The base layer and the strengthening layer are both composed of an aluminum matrix and a composite reinforcement material;
[0038] The aluminum matrix of the base layer is an aluminum-magnesium-silicon alloy, and the addition amount of magnesium is 3-7%, the addition amount of silicon is 7-11%, and the rest is aluminum and unavoidable impurities.
[0039] The composite reinforcement material of the base layer comprises, by volume fraction, 10-20% of SiC particles, 0.3-0.7% of carbon nanofibers, 0.1-0.2% of graphene nanosheets, and 3-5% of alumina short fibers;
[0040] The aluminum matrix of the strengthening layer is an aluminum-zinc-magnesium-copper alloy, and the addition amount of zinc is 8-12%, the addition amount of magnesium is 2-4%, the addition amount of copper is 1-3%, and the rest is aluminum and unavoidable impurities.
[0041] The composite reinforcement material of the strengthening layer comprises, by volume fraction, 25-35% of SiC particles, 5-10% of barium titanate particles, 8-12% of boron nitride fibers, 0.3-0.6% of carbon nanofibers and 0.15-0.25% of graphene nanosheets, and 2-4% of zirconium oxide particles;
[0042] The porous structure layer is composed of a three-dimensional porous skeleton made of 7075 aluminum alloy;
[0043] The aluminum matrix and the composite reinforcement material are bonded by means of a polyimide resin containing 10% of glass fiber.
[0044] The polyimide resin containing glass fibers is composed of a polyimide resin matrix, glass fibers and a small amount of curing agent, wherein the content of the glass fibers is 10%, and the amount of the curing agent added is determined according to the curing requirements of the resin.
[0045] The aluminum matrix raw materials of the base layer and the strengthening layer need to be homogenized before preparation to improve the distribution uniformity of the alloy elements.
[0046] The three-dimensional porous skeleton of the porous structure layer is prepared by powder metallurgy or 3D printing technology, and has uniform porosity and good mechanical properties.
[0047] A method for preparing an aluminum-based composite plate according to any one of the above, the method comprising the following steps:
[0048] S1: Raw material preparation and pretreatment: Prepare the raw materials of the base layer, porous structure layer, strengthening layer and protective coating according to the ratio, and clean and pretreat the raw materials;
[0049] S2: Preparation of base and reinforcement layer blanks: The aluminum matrix raw materials of the base and reinforcement layers are uniformly mixed with the corresponding composite reinforcement materials, and are prepared into blanks by hot pressing sintering or powder metallurgy process;
[0050] S3: Preparation of porous structure layer: Prepare a three-dimensional porous skeleton of 7075 aluminum alloy by powder metallurgy or 3D printing technology to form a porous structure layer;
[0051] S4: Lamination and pre-pressing: The base layer, the porous structure layer and the reinforcement layer are stacked in order, and polyimide resin containing glass fiber is evenly applied between the layers as a binder, and then pre-pressing is performed;
[0052] S5: Curing: Curing the pre-pressed sample at an appropriate temperature and pressure to completely cure the polyimide resin containing glass fibers;
[0053] S6: Heat treatment: The cured sample is heat treated to improve its mechanical properties and thermal stability;
[0054] S7: Protective coating treatment: The surface of the aluminum-based composite sheet after heat treatment is treated with aluminum-zinc alloy to improve its corrosion resistance and aesthetics.
[0055] Embodiment 2:
[0056] The aluminum-based composite plate of this embodiment is substantially the same as the aluminum-based composite plate of Example 1, except that in the aluminum matrix of the base layer, the addition amount of magnesium is 3%, the addition amount of silicon is 7%, and the rest is aluminum and unavoidable impurities;
[0057] The composite reinforcement material of the base layer contains 10% SiC particles, 0.3% carbon nanofibers, 0.1% graphene nanosheets, and 3% alumina short fibers;
[0058] In the aluminum matrix of the strengthening layer, the addition amount of zinc is 8%, the addition amount of magnesium is 2%, the addition amount of copper is 1%, and the rest is aluminum and unavoidable impurities;
[0059] The composite reinforcement material of the strengthening layer includes 25% SiC particles, 5% barium titanate particles, 8% boron nitride fibers, 0.3% carbon nanofibers, 0.15% graphene nanosheets, and 2% zirconium oxide particles.
[0060] Embodiment 3:
[0061] The aluminum-based composite plate of this embodiment is substantially the same as the aluminum-based composite plate of Example 1, except that in the aluminum matrix of the base layer, the addition amount of magnesium is 4%, the addition amount of silicon is 8%, and the rest is aluminum and unavoidable impurities;
[0062] The composite reinforcement material of the base layer contains 12% SiC particles, 0.4% carbon nanofibers, 0.12% graphene nanosheets, and 3.5% alumina short fibers;
[0063] In the aluminum matrix of the strengthening layer, the addition amount of zinc is 9%, the addition amount of magnesium is 2%, the addition amount of copper is 1.5%, and the rest is aluminum and unavoidable impurities;
[0064] The composite reinforcement material of the strengthening layer includes 27% SiC particles, 6% barium titanate particles, 9% boron nitride fibers, 0.4% carbon nanofibers, 0.17% graphene nanosheets, and 2.5% zirconium oxide particles.
[0065] Embodiment 4:
[0066] The aluminum-based composite plate of this embodiment is substantially the same as the aluminum-based composite plate of Example 1, except that in the aluminum matrix of the base layer, the addition amount of magnesium is 6%, the addition amount of silicon is 10%, and the rest is aluminum and unavoidable impurities;
[0067] The composite reinforcement material of the base layer contains 17% SiC particles, 0.6% carbon nanofibers, 0.17% graphene nanosheets, and 4.5% alumina short fibers;
[0068] In the aluminum matrix of the strengthening layer, the addition amount of zinc is 11%, the addition amount of magnesium is 3%, the addition amount of copper is 2.5%, and the rest is aluminum and unavoidable impurities;
[0069] The composite reinforcement material of the strengthening layer includes 32% SiC particles, 8% barium titanate particles, 11% boron nitride fibers, 0.5% carbon nanofibers, 0.22% graphene nanosheets, and 3.5% zirconium oxide particles.
[0070] Embodiment 5:
[0071] The aluminum-based composite plate of this embodiment is substantially the same as the aluminum-based composite plate of Example 1, except that in the aluminum matrix of the base layer, the addition amount of magnesium is 7%, the addition amount of silicon is 11%, and the rest is aluminum and unavoidable impurities;
[0072] The composite reinforcement material of the base layer contains 20% SiC particles, 0.7% carbon nanofibers, 0.2% graphene nanosheets, and 5% alumina short fibers;
[0073] In the aluminum matrix of the strengthening layer, the addition amount of zinc is 12%, the addition amount of magnesium is 4%, the addition amount of copper is 3%, and the rest is aluminum and unavoidable impurities;
[0074] The composite reinforcement material of the strengthening layer includes 35% SiC particles, 10% barium titanate particles, 12% boron nitride fibers, 0.6% carbon nanofibers, 0.25% graphene nanosheets, and 4% zirconium oxide particles.
[0075] Comparative Example 1:
[0076] The aluminum-based composite plate of this comparative example is substantially the same as the aluminum-based composite plate of Example 1, except that the amount of magnesium added to the aluminum matrix of the base layer of this comparative example is 5-9%.
[0077] Comparative Example 2:
[0078] The aluminum-based composite plate material of this comparative example is substantially the same as the aluminum-based composite plate material of Example 1, except that the amount of silicon added to the aluminum matrix of the base layer of this comparative example is 9-13%.
[0079] Comparative Example 3:
[0080] The aluminum-based composite plate of this comparative example is substantially the same as the aluminum-based composite plate of Example 1, except that the composite reinforcement material of the base layer of this comparative example contains 15-25% SiC particles.
[0081] Comparative Example 4:
[0082] The aluminum-based composite plate of this comparative example is substantially the same as the aluminum-based composite plate of Example 1, except that the composite reinforcement material of the base layer of this comparative example contains 0.5-1% of carbon nanofibers.
[0083] Comparative Example 5:
[0084] The aluminum-based composite plate material of this comparative example is substantially the same as the aluminum-based composite plate material of Example 1, except that the composite reinforcement material of the base layer of this comparative example contains 0.4-0.5% of graphene nanosheets.
[0085] Comparative Example 6:
[0086] The aluminum-based composite plate material of this comparative example is substantially the same as the aluminum-based composite plate material of Example 1, except that the composite reinforcement material of the base layer of this comparative example contains 4-7% of alumina short fibers.
[0087] Comparative Example 7:
[0088] The aluminum-based composite plate of this comparative example is substantially the same as the aluminum-based composite plate of Example 1, except that in this comparative example, the amount of zinc added to the aluminum matrix of the strengthening layer is 10-14%.
[0089] Comparative Example 8:
[0090] The aluminum-based composite plate of this comparative example is substantially the same as the aluminum-based composite plate of Example 1, except that in this comparative example, the amount of magnesium added to the aluminum matrix of the strengthening layer is 3-5%.
[0091] Comparative Example 9:
[0092] The aluminum-based composite plate of this comparative example is substantially the same as the aluminum-based composite plate of Example 1, except that in this comparative example, the amount of copper added to the aluminum matrix of the strengthening layer is 3-5%.
[0093] Comparative Example 10:
[0094] The aluminum-based composite plate of this comparative example is substantially the same as the aluminum-based composite plate of Example 1, except that the composite reinforcement material of the strengthening layer of this comparative example contains 35-45% SiC particles.
[0095] Comparative Example 11:
[0096] The aluminum-based composite plate material of this comparative example is substantially the same as the aluminum-based composite plate material of Example 1, except that the composite reinforcement material of the strengthening layer of this comparative example contains 8-13% of barium titanate particles.
[0097] Comparative Example 12:
[0098] The aluminum-based composite plate material of this comparative example is substantially the same as the aluminum-based composite plate material of Example 1, except that the composite reinforcement material of the strengthening layer of this comparative example contains 5-9% of boron nitride fibers.
[0099] Comparative Example 13:
[0100] The aluminum-based composite plate material of this comparative example is substantially the same as the aluminum-based composite plate material of Example 1, except that the composite reinforcement material of the strengthening layer of this comparative example contains 0.5-0.9% of carbon nanofibers.
[0101] Comparative Example 13:
[0102] The aluminum-based composite plate material of this comparative example is substantially the same as the aluminum-based composite plate material of Example 1, except that the composite reinforcement material of the strengthening layer of this comparative example contains 0.2-0.4% of graphene nanosheets.
[0103] Comparative Example 14:
[0104] The aluminum-based composite plate material of this comparative example is substantially the same as the aluminum-based composite plate material of Example 1, except that the composite reinforcement material of the strengthening layer of this comparative example contains 3-5% of zirconium oxide particles.
[0105] The aluminum-based composite plate materials prepared in the above-mentioned Examples 2-5 and Comparative Examples 1-14 were used to prepare aluminum-based composite plates according to the preparation method of Example 1, and the performance of the prepared plates was tested. The specific results can be seen in Table 1:
[0106] Table 1:
[0107]
[0108]
[0109]
[0110] As can be seen from the table, the overall mechanical properties of the material are enhanced by the present invention, and the mechanical properties and thermal stability of the material are significantly improved by optimizing the material composition and structure, which has significant technical advantages and application value.
[0111] The embodiments of the present invention disclose preferred embodiments, but are not limited thereto. A person skilled in the art can easily understand the spirit of the present invention based on the above embodiments and make different extensions and changes. However, as long as they do not deviate from the spirit of the present invention, they are all within the protection scope of the present invention.
Claims
1. An aluminum-based silicon carbide composite plate strip, characterized in that: From the inside to the outside, it includes: base layer, porous structure layer, strengthening layer and protective coating: The base layer and the strengthening layer are both composed of an aluminum matrix and a composite reinforcement material; The aluminum matrix of the base layer is an aluminum-magnesium-silicon alloy, and the addition amount of magnesium is 3-7%, the addition amount of silicon is 7-11%, and the rest is aluminum and unavoidable impurities. The composite reinforcement material of the base layer comprises, by volume fraction, 10-20% of SiC particles, 0.3-0.7% of carbon nanofibers, 0.1-0.2% of graphene nanosheets, and 3-5% of alumina short fibers; The aluminum matrix of the strengthening layer is an aluminum-zinc-magnesium-copper alloy, and the addition amount of zinc is 8-12%, the addition amount of magnesium is 2-4%, the addition amount of copper is 1-3%, and the rest is aluminum and unavoidable impurities. The composite reinforcement material of the strengthening layer comprises, by volume fraction, 25-35% of SiC particles, 5-10% of barium titanate particles, 8-12% of boron nitride fibers, 0.3-0.6% of carbon nanofibers and 0.15-0.25% of graphene nanosheets, and 2-4% of zirconium oxide particles; The porous structure layer is composed of a three-dimensional porous skeleton made of 7075 aluminum alloy; The aluminum matrix and the composite reinforcement material are bonded by means of a polyimide resin containing 10% of glass fiber.
2. The aluminum-based silicon carbide composite strip according to claim 1, characterized in that: The polyimide resin containing glass fibers is composed of a polyimide resin matrix, glass fibers and a small amount of curing agent, wherein the content of the glass fibers is 10%, and the amount of the curing agent added is determined according to the curing requirements of the resin.
3. The aluminum-based silicon carbide composite strip according to claim 1, characterized in that: The aluminum matrix raw materials of the base layer and the strengthening layer need to be homogenized before preparation to improve the distribution uniformity of the alloy elements.
4. The aluminum-based silicon carbide composite strip according to claim 1, characterized in that: The three-dimensional porous skeleton of the porous structure layer is prepared by powder metallurgy or 3D printing technology, and has uniform porosity and good mechanical properties.
5. A method for preparing an aluminum-based composite sheet material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: S1: Raw material preparation and pretreatment: Prepare the raw materials of the base layer, porous structure layer, strengthening layer and protective coating according to the ratio, and clean and pretreat the raw materials; S2: Preparation of base and reinforcement layer blanks: The aluminum matrix raw materials of the base and reinforcement layers are uniformly mixed with the corresponding composite reinforcement materials, and are prepared into blanks by hot pressing sintering or powder metallurgy process; S3: Preparation of porous structure layer: Prepare a three-dimensional porous skeleton of 7075 aluminum alloy by powder metallurgy or 3D printing technology to form a porous structure layer; S4: Lamination and pre-pressing: The base layer, the porous structure layer and the reinforcement layer are stacked in order, and polyimide resin containing glass fiber is evenly applied between the layers as a binder, and then pre-pressing is performed; S5: Curing: Curing the pre-pressed sample at an appropriate temperature and pressure to completely cure the polyimide resin containing glass fibers; S6: Heat treatment: The cured sample is heat treated to improve its mechanical properties and thermal stability; S7: Protective coating treatment: The surface of the aluminum-based composite sheet after heat treatment is treated with aluminum-zinc alloy to improve its corrosion resistance and aesthetics.
6. The method for preparing an aluminum-based composite plate according to claim 5, characterized in that: In step S2, the base layer and the strengthening layer are prepared by hot isostatic pressing sintering process, and the sintering is carried out at a temperature of 1300-1500° C. and a pressure of 150-250 MPa.
7. The method for preparing an aluminum-based composite plate according to claim 5, characterized in that: In step S4, the pre-pressing treatment pressure is 20-40 MPa, and the pre-pressing time is 30-60 minutes.
8. The method for preparing an aluminum-based composite plate according to claim 5, characterized in that: In step S6, the heat treatment includes two steps: solution treatment and aging treatment. The solution treatment temperature is 480-520°C and the holding time is 24 hours; the aging treatment temperature is 160-200°C and the holding time is 48 hours.
Citation Information
Patent Citations
Laminar composite and preparation method thereof
CN106079739A
Method for uniformly dispersing discontinuous reinforcements in high-strength aluminum alloy
CN115229197A
Lightweight high-strength aluminum-based composite board as well as preparation method and application thereof
CN117656609A
Aluminum-based composite plate with multilayer structure
CN209336213U
Multilayer plate with composite material and method for manufacturing the same
US20210370643A1